The Effect Of Lavender Aromatherapy On The Intensity Of Menstrual Pain In Adolescent Girls - Ika Nur Saputri; Sari, Mayang (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Until now, dysmenorrhea is still a frightening threat for women, especially young women, when they are approaching menstruation. Pain that occurs during menstruation is a result of excessive uterine contractions caused by the hormone prostaglandin. One non-pharmacological method used to reduce the intensity of pain is by using lavender aromatherapy. Aromatherapy can be given through inhalation or direct application to the skin through massage using inner oil. Aromatherapy is believed to be useful in treating respiratory problems, pain, and mental and emotional problems. The main aim of the research was to see how pain intensity decreased in teenagers before and after being given lavender aromatherapy. This quasi-experimental research used a one group pre-post and post-test approach with samples taken based on purposive sampling according to the specified criteria of 33 people. The results of the Shapiro Wilk test showed that the average pain scale before treatment was 6.52. Then the average pain scale dropped to 4.30 after being given lavender aromatherapy. The calculated Z value is 5.150 and the p-value is 0.000, thus providing significant results that there is an effect of giving lavender aromatherapy on the intensity of menstrual pain in young women at SMA Negeri 1 Perbaungan. In the future, it is hoped that lavender aromatherapy can continue to develop its properties and benefits for teenagers who have problems with pain during menstruation or related health problems.